Experimental Observation of PT Soliton Collapse in 2D Synthetic Lattice - Muniz, Andre L.M.; Wimmer, Martin; Bisianov, Arstan; Morandotti, R.; Peschel, Ulf (2019 Conference on Lasers and Electro-Optics, CLEO 2019 - Proceedings, 2019)
Using standard telecommunication equipment, we experimentally realize Parity-Time symmetry in a two-dimensional synthetic lattice with tunable gain, loss and phase structure. The fiber nonlinearity enables PT soliton collapse as an amplified, self-accelerating nonlinear wave packet.
CRIS-Team Scopus Importer:2023-04-20